Prognostic role of patient gender in limited-disease small-cell lung cancer treated with chemoradiotherapy - Roengvoraphoj, Olarn; Eze, Chukwuka; Niyazi, Maximilian; Li, Minglun; Hildebrandt, Guido; Fietkau, Rainer; Belka, Claus; Manapov, Farkhad (Strahlentherapie und Onkologie, 2017)
BACKGROUND: Previous studies have demonstrated that female gender could be a prognostic factor in limited-disease (LD) small-cell lung cancer (SCLC), but the correlation between patient gender and survival parameters remains unclear. PATIENTS AND METHODS: Data from 179 LD SCLC patients treated with definitive chemoradiotherapy (CRT) were reviewed. Influence of patient gender on time to progression (TTP), local control (LC), brain metastasis-free (BMFS), distant metastasis-free (DMFS) and overall survival (OS) was analysed. RESULTS: Definitive CRT was completed by 179 (110 men/69 women) patients. Of these, 68 (38%; 34 men/34 women) patients were treated in concurrent and 111 (62%; 76 men/35 women) in sequential mode. Prophylactic cranial irradiation (PCI) was subsequently applied in 70 (39%; 36 men/34 women) patients with partial or complete response after CRT. Median OS was 20 (95% confidence interval [CI] 10-22) and 14 (95% CI 10-18) months in female and male patients, respectively (p = 0.021). In subgroups defined by remission status (complete and partial response) after CRT, an OS benefit for females compared to males was also detected. There was no correlation between patient gender and TTP, LC or DMFS, and no difference in OS in the female and male subgroups treated with PCI. The incidence of metachronous brain metastases (BMs) in the male and female subgroups differed significantly (40/110 men vs. 18/69 women, p = 0.03). Also, mean BMFS was significantly longer in women (p = 0.023). Patient gender also significantly correlated with OS on multivariate analysis after adjustment for other prognostic factors (p = 0.04, HR 1.38, 95% CI 1.08-1.92). CONCLUSION: In this heterogeneous LD SCLC patient cohort treated with definitive CRT, female gender was significantly associated with longer BMFS and OS, as well as with a lower incidence of metachronous brain failure.
EVALuna2:32912